Neural Marker of Habituation at 5 Months of Age Associated with Deferred Imitation Performance at 12 Months: A Longitudinal Study in the UK and The Gambia - Laura Katus; Bosiljka Milosavljevic; Maria Rozhko; Samantha McCann; Luke Mason; Ebrima Mbye; Ebou Touray; Sophie E. Moore; Clare E. Elwell; Sarah Lloyd-Fox; Michelle de Haan; The BRIGHT Study Team (MDPI AG, 2022)
Across cultures, imitation provides a crucial route to learning during infancy. However, neural predictors which would enable early identification of infants at risk of suboptimal developmental outcomes are still rare. In this paper, we examine associations between ERP markers of habituation and novelty detection measured at 1 and 5 months of infant age in the UK (n = 61) and rural Gambia (n = 214) and infants' responses on a deferred imitation task at 8 and 12 months. In both cohorts, habituation responses at 5 months significantly predicted deferred imitation responses at 12 months of age in both cohorts. Furthermore, ERP habituation responses explained a unique proportion of variance in deferred imitation scores which could not be accounted for by a neurobehavioural measure (Mullen Scales of Early Learning) conducted at 5 months of age. Our findings highlight the potential for ERP markers of habituation and novelty detection measured before 6 months of age to provide insight into later imitation abilities and memory development across diverse settings.